The Hemagglutinin of Bat-Associated Influenza Viruses Is Activated by TMPRSS2 for pH-Dependent Entry into Bat but Not Human Cells - Hoffmann, Markus (PLoS One, 2016)
New World bats have recently been discovered to harbor influenza A virus (FLUAV)-related viruses, termed bat-associated influenza A-like viruses (batFLUAV). The internal proteins of batFLUAV are functional in mammalian cells. In contrast, no biological functionality could be demonstrated for the surface proteins, hemagglutinin (HA)-like (HAL) and neuraminidase (NA)-like (NAL), and these proteins need to be replaced by their human counterparts to allow spread of batFLUAV in human cells. Here, we employed rhabdoviral vectors to study the role of HAL and NAL in viral entry. Vectors pseudotyped with batFLUAV-HAL and -NAL were able to enter bat cells but not cells from other mammalian species. Host cell entry was mediated by HAL and was dependent on prior proteolytic activation of HAL and endosomal low pH. In contrast, sialic acids were dispensable for HAL-driven entry. Finally, the type II transmembrane serine protease TMPRSS2 was able to activate HAL for cell entry indicating that batFLUAV can utilize human proteases for HAL activation. Collectively, these results identify viral and cellular factors governing host cell entry driven by batFLUAV surface proteins. They suggest that the absence of a functional receptor precludes entry of batFLUAV into human cells while other prerequisites for entry, HAL activation and protonation, are met in target cells of human origin.